Advantages of day‐before lymphoscintigraphy and undiluted methylene blue dye injections for sentinel lymph node biopsies for melanoma. Issue 8 (16th September 2016) - Dinh, Kate H.; Harris, Ariana F.; LaFemina, Jennifer; Whalen, Giles F.; Sullivan, Mary; Licho, Robert; Hill, Thomas; Lambert, Laura A.
Abstract : Background and Objectives: Lymphatic mapping (LM) and blue dye injections are essential to identification of sentinel lymph nodes (SLN) for melanoma. LM is performed the day before (DB) or the same day (SD) of surgery, but the optimal timing is unknown. Similarly, methylene blue (MB), used during SLN biopsy (SLNB), is administered diluted (dMB) or undiluted (uMB), but the relative efficacies are unknown. Methods: Patients who underwent SLNB for melanoma from 2009 to 2013 at our institution were evaluated. Outcomes included operative correlation with LM, SLN identification, and postoperative complications. Results: One hundred seventy‐one patients underwent SLNB. Sixty‐seven (39%) had DB LM. Sixty‐seven (39%) received uMB. Operative findings correlated with both LM groups, though the DB patients had lower background count ( P = 0.018) and lower highest SLN radioactive signal count ( P = 0.046). More uMB patients had blue SLNs (90% vs. 68%, P = 0.001). There was no difference in the total number of SLNs or complication rates in the LM and MB groups. Conclusions: This is the first study to compare the use of DB LM with SD LM and the efficacy of uMB versus dMB. DB LM and uMB offer advantageous alternatives for patients and their surgeons without loss of accuracy or increased morbidity. J. Surg. Oncol. 2016;114:947–950 . © 2016 Wiley Periodicals, Inc.